Extended Opa Model for Cascading Failure Analyzes - Dedinec Kanevche, Aleksandra; Mishkovski, Igor; Kocarev, Ljupco (Faculty of Computer Science and Engineering, Ss. Cyril and Methodius University in Skopje, Macedonia, 2012)
In this paper the reliability of networks and especially the cascading failures are analyzed. As a special type of network the electric power grid is considered. The network is modeled (taking into account the nature of electricity networks) using linear programming dispatch of the generated electricity to the consumers. The data of the electric power system of Southeast Europe are used. The reliability of the network is analyzed using the OPA model which enables cascading failure analyzes based on probabilistic outages of the overloaded lines and includes long-term upgrading of the system in response to the increased electricity demand over the time. In this paper, the OPA model is extended to include the minimum generation capacity of each power plant and it is analyzed how this constraint affects the cascading failures. The results show that this constraint introduces additional instability in the system that leads to higher cascading failures of the power transmission lines